-5h-17=-8(h+4)

Simple and best practice solution for -5h-17=-8(h+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5h-17=-8(h+4) equation:



-5h-17=-8(h+4)
We move all terms to the left:
-5h-17-(-8(h+4))=0
We calculate terms in parentheses: -(-8(h+4)), so:
-8(h+4)
We multiply parentheses
-8h-32
Back to the equation:
-(-8h-32)
We get rid of parentheses
-5h+8h+32-17=0
We add all the numbers together, and all the variables
3h+15=0
We move all terms containing h to the left, all other terms to the right
3h=-15
h=-15/3
h=-5

See similar equations:

| -7=-4(p+8)+3(-p-8 | | 1/2x+17=4x+2 | | y=12*9+5 | | −68x+68=-68x+34 | | -5h-17=-8(h=4) | | 2/x+5=x+8/9 | | 4(5x-10)+2(2x+10)=124 | | -7(6x+4)+3(4-x)=-61 | | X+1/12=5/6+x-2/3 | | 0.025p-1=0.15​(p-5​) | | 7(m-4)(m+1)=-34 | | 58-3a=10 | | 59=2-3(4x+1) | | -5t+7=11t-24 | | 4y-(-3)=-25 | | 3/x+12=53 | | 3n=6n-3(5n+4) | | 7x-5=5(x-2)+13 | | 0=7(3n-7)-4(-8n+1) | | −68x+34=-68x+34 | | -7v-8=2v-6 | | -3=÷-4w+26 | | 3+3n=8n+3 | | -3-3(1+7k)=6(4-6k) | | -20+8x=x+15 | | y/10=254 | | 27=9/2(t | | 2/3x=15+x | | X/4–4=3x–6 | | 4-x=3(5x+12) | | 14/3x=1,386 | | -3-3(1+7k)=6(4-6k |

Equations solver categories